Kiulu bed and breakfast / Finella Vera Maurice... [et al.] - Maurice, Finella Vera; Ephen, Trecy Penny; Ignatius Moskul, Florina; Mogindol, Terrence Boyo; AK Mohiddin, DK Rafidzah (Faculty of Applied Sciences, 2004)
First and foremost, we the members of KIULU BED AND BREAKFAST are glad because the preparations and the hard work for this business proposal has come to a satisfying result as well as fact that we manage to finish it right on time with all the requirements being fulfilled. We thank God for his blessings and for making the whole thing possible by providing us great mind people and people to work with. The business had taught us A lot particularly in the process of making up a business. With this knowledge that we have now, we are sure that it will benefit us in the future. We have faced with a lot of challenges during the whole process of this proposal and we have a lot of experiences with the real world. Of where some entrepreneurs are hesitate to give information about their business, afraid that it will affect their business. However, with great commitment and understanding among group members, the whole thing works out very fine. With the help of other individuals, we are able to finish this proposal with satisfying outcome. Last but not least, hopefully this business proposal will provide information as well as guidelines to others who are going to be entrepreneur. We also hope that it will serve as reference to those who are going to prepare business proposal in the future.